Upaya Peningkatan Pengetahuan Ibu tentang Perawatan Payudara Selama Hamil - Sri Maharani (Jurnal Abdimas Kesehatan (JAK), 2020)
Breast care during pregnancy is one important part that must be considered as preparation for breastfeeding later. Breasts need to be prepared since pregnancy so that if the baby is born it can function properly immediately when needed. Breast care is also very helpful in the success of early breastfeeding, which affects exclusive breastfeeding. Breast care (Breast Care) is a way of caring for breasts performed during pregnancy or the puerperium for the production of breast milk, other than that for cleanliness of the breast and the form of nipples that go in or flat. Nipples are actually not an obstacle for mothers to breastfeed well by knowing from the beginning, mothers have time to make it easier for nipples to breastfeed. Besides that it is also very important to pay attention to personal hygiene. Current problems faced by partners include the lack of knowledge of pregnant women regarding the importance of breast care during pregnancy, so it is considered necessary to provide counseling to provide knowledge to pregnant women to prepare pregnant women to give early breastfeeding at the time of delivery and provide exclusive breastfeeding to infants up to 2 years. Community service activities are carried out at the Puskesmas Putri Ayu Kota Jambi. Time of implementation in January 2019. The target is pregnant women. Community service methods survey approach, lecture, discussion, demonstration / simulation. The results obtained are pregnant women able to understand about the benefits of breast care during pregnancy. It is recommended for health workers, especially in Puskesmas to give more information about breast care to pregnant women by participating in activities carried out in the village and RT so that pregnant women get information about breast care and can prepare for early breastfeeding to infants properly.